TET2-mediated Cdkn2A DNA hydroxymethylation in midbrain dopaminergic neuron injury of Parkinson's disease. (10th February 2020) - Wu, Ting-Ting; Liu, Te; Li, Xuan; Chen, Ya-Jing; Chen, Tian-Jiao; Zhu, Xiao-Ying; Chen, Jiu-Lin; Li, Qing; Liu, Ye; Feng, Ya; Wu, Yun-Cheng
Abstract: It has been reported that abnormal epigenetic modification is associated with the occurrence of Parkinson's disease (PD). Here, we found that a ten-eleven translocation 2 (TET2), a staff of the DNA hydroxylases family, was increased in dopaminergic neurons in vitro and in vivo . Genome-wide mapping of DNA 5-hydroxymethylcytosine (5-hmC)-sequencing has revealed an aberrant epigenome 5-hmC landscape in 1-methyl-4-phenylpyridinium iodide (MPP + )-induced SH-SY5Y cells. The TET family of DNA hydroxylases could reverse DNA methylation by oxidization of 5-methylcytosine (5-mC) to 5-hmC. However, the relationship between modification of DNA hydroxymethylation and the pathogenesis of PD is not clear. According to the results of 5-hmC-sequencing studies, 5-hmC was associated with gene-rich regions in the genomes related to cell cycle, especially gene-cyclin-dependent kinase inhibitor 2A ( Cdkn2A ). Downregulation of TET2 expression could significantly rescue MPP + -stimulated SH-SY5Y cell damage and cell cycle arrest. Meanwhile, knockdown of Tet2 expression in the substantia nigra pars compacta of MPTP-induced PD mice resulted in attenuated MPTP-induced motor deficits and dopaminergic neuronal injury via p16 suppression. In this study, we demonstrated a critical function of TET2 in PD development via the CDKN2A activity-dependent epigenetic pathway, suggesting a potential new strategy for epigenetic therapy.